Goat in a boat: first reading fun - Harker, Jillian; Smith, Jan (Autumn Pub. Chichester, 2010)
This charming story features a goat who embarks on an unexpected boating adventure. As he navigates the waters, he encounters various quirky characters and situations, all told in a fun, rhythmic style. The book highlights themes of curiosity and friendship, making it an enjoyable read for young children.